La importancia del lenguaje y el aprendizaje en el desarrollo del niño - Calderón Coronado, Raquel (2016)
Language is one of the fundamental aspects in the development of the child, it is the wonderful soul that opens thousands of doors to other knowledge, is the tool of relation with others and allows properly interacting. The first place where this language has to develop will be in the family, in the first interactions with the mother, in those first babbling and that gradually develops, at the same time, with its entrance to the school evolves more and more until reaching its maximum development. It is therefore the fundamental task of families, parents to try to develop it and to identify the difficulties that their babies can present to go to a specialist as soon as possible. On the other hand, Early Education teachers not onlymust be attentive to the difficulties that their students may present, but must seek to develop their verbal potential as much as possible.